EVALUATION OF NUSANTARA 3 REMOTELY OPERATED VEHICLE (N3-ROV) SPECIAL REPORT OF PERFORMANCE AND STABILITY IN VARIOUS WATER CONDITIONS: EVALUASI KINERJA DAN STABILITAS NAVIGASI NUSANTARA 3 REMOTELY OPERATED VEHICLE (N3-ROV) DALAM LINGKUNGAN PERAIRAN BERBEDA - Pratama, Xavercius Cezar; Jaya, Indra; Iqbal, Muhammad (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Vast marine resources require underwater observation and exploration, but conventional diving methods have many risks. Therefore, developing underwater technology such as Remotely Operated Underwater Vehicles (ROV) is essential to reduce the risk. However, the unpredictable underwater environment requires ROV performance testing before optimal use. Therefore, this study was conducted to test the performance of the N3-ROV, determine its specific specifications, and design a control system and video acquisition so that it can be an alternative for underwater observation and exploration. The N3-ROV has dimensions of 61x65x34 cm, a total weight of 13 kg, with a buoyancy of 128.4 kg.m/s², with surface control using a gamepad connected to a laptop. Performance tests were carried out in two different environments, a pool environment and a field environment. The N3-ROV has a straight movement in the pool environment with an error of 0° and in the field environment of 1.7° with speeds of 76.6 cm/s and 77.2 cm/s, respectively. The descent motion in both environments is different, where in the pool environment, the descent motion has a delay and error of 9.7 seconds and 94.1°, respectively, compared to the field environment of 3.9 seconds and 48.8°. The delay and error in the turning motion in the pool environment are higher than in the sea environment. The gliding motion in the pool environment has a slower surfacing speed compared to the field environment.